2019
DOI: 10.31470/2309-1797-2019-25-2-50-68
|View full text |Cite
|
Sign up to set email alerts
|

Language Changes in Late-Onset Alzheimer’s Disease

Abstract: Alzheimer’ s disease (AD) is the most common cause of cognitive decline and dementia in the elderly. Language disturbances appear early in AD and constitute an important element of the diagnosis, although they are usually overshadowed by impairment of memory and executive functions. It is known that language is impaired disproportionally in AD: the semantic and pragmatic language systems are more impaired than syntax. However, syntactic features can also be impaired in the moderate and severe stages of AD. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Only a small portion of studies have investigated AD abilities on sentence production and morphosyntactic production abilities (as cited in Curti, 2020). In some researches, the sentence production of AD patients were analysed and it was revealed that AD patients tended to use simple sentence structures more compared to the complex sentence structures (Can & Kuruoglu, 2017, 2018a, 2018b, 2019a, 2019b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a small portion of studies have investigated AD abilities on sentence production and morphosyntactic production abilities (as cited in Curti, 2020). In some researches, the sentence production of AD patients were analysed and it was revealed that AD patients tended to use simple sentence structures more compared to the complex sentence structures (Can & Kuruoglu, 2017, 2018a, 2018b, 2019a, 2019b.…”
Section: Discussionmentioning
confidence: 99%
“…In some of research which are related to the sentence length and complex sentence structures, it is revealed that the performance of AD patients' on syntactic ability differs from the healthy people. Moreover, these differences can also been observed on the two subtypes of AD as late-onset and early-onset (Can & Kuruoglu, 2017, 2018a, 2018b, 2019a, 2019b).…”
Section: Performance On the Picture Description Tasks In Patients Witmentioning
confidence: 94%
“…Only a small portion of studies have investigated AD abilities on sentence production and morphosyntactic production abilities (as cited in Curti, 2020). In some researches, the sentence production of AD patients were analysed and it was revealed that AD patients tended to use simple sentence structures more compared to the complex sentence structures (Can & Kuruoglu, 2017, 2018a, 2018b, 2019a, 2019b.…”
Section: Discussionmentioning
confidence: 99%
“…In some of research which are related to the sentence length and complex sentence structures, it is revealed that the performance of AD patients' on syntactic ability differs from the healthy people. Moreover, these differences can also been observed on the two subtypes of AD as late-onset and early-onset (Can & Kuruoglu, 2017, 2018a, 2018b, 2019a, 2019b.…”
Section: виконання задач опису зображення у хворих на пізній стадії д...mentioning
confidence: 95%